2020
DOI: 10.3390/ijms21239092
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Kingella kingae RtxA Toxin Depends on Cell Surface Oligosaccharides, but Not on β2 Integrins

Abstract: The Gram-negative coccobacillus Kingella kingae is increasingly recognized as an important invasive pediatric pathogen that causes mostly bacteremia and skeletal system infections. K. kingae secretes an RtxA toxin that belongs to a broad family of the RTX (Repeats in ToXin) cytotoxins produced by bacterial pathogens. Recently, we demonstrated that membrane cholesterol facilitates interaction of RtxA with target cells, but other cell surface structures potentially involved in toxin binding to cells remain unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…All these results showed that glycosylated structures on the cell surface and membrane cholesterol together act as the major membrane components used by RtxA to interact with target cells. Since glycosylated structures are present on the surface of all mammalian cells and cholesterol is a key structural component of all animal membranes, our results explain the previously observed promiscuity of RtxA binding to a wide spectrum of cells from various species and indicated that RtxA can be classified as a broadly cytolytic RTX hemolysin [37,262].…”
Section: β 2 Integrin Receptor-independent Interactionsupporting
confidence: 80%
See 4 more Smart Citations
“…All these results showed that glycosylated structures on the cell surface and membrane cholesterol together act as the major membrane components used by RtxA to interact with target cells. Since glycosylated structures are present on the surface of all mammalian cells and cholesterol is a key structural component of all animal membranes, our results explain the previously observed promiscuity of RtxA binding to a wide spectrum of cells from various species and indicated that RtxA can be classified as a broadly cytolytic RTX hemolysin [37,262].…”
Section: β 2 Integrin Receptor-independent Interactionsupporting
confidence: 80%
“…Based on the cited literature showing that several RTX toxins specifically interact with the β 2 integrins on the cell surface, we recently investigated whether the β 2 integrins could also be the potential receptors for the RTX cytolysin RtxA [ 262 ]. We examined the binding and cytotoxicity of RtxA on CHO cells that ectopically expressed three different human β 2 integrins, CD11a/CD18, CD11b/CD18, or CD11c/CD18.…”
Section: Interaction Of Rtxa and Other Rtx Toxins With Target Cellsmentioning
confidence: 99%
See 3 more Smart Citations